Implementation of guideline‐recommended medical therapy for patients with heart failure in Europe - Maurizio Volterrani; Petar Seferovic; Gianluigi Savarese; Ilaria Spoletini; Egidio Imbalzano; Antoni Bayes‐Genis; Ewa Jankowska; Michele Senni; Marco Metra; Ovidiu Chioncel; Andrew J. S. Coats; Giuseppe M. C. Rosano (ESC Heart Failure)
Abstract Physicians' adherence to guideline‐recommended heart failure (HF) treatment remains suboptimal, especially regarding the target doses. In particular, there is evidence that non‐cardiologists are less compliant with HF guideline recommendations. This is likely to have a detrimental impact on patients' survival, readmissions and quality of life. Thus, the present document aims to address the reasons underlying low implementation and under‐dosing of guideline‐directed medical therapy in HF and to update a guidance for the initiation and rapid titration of HF drugs. In particular, aim of this document is to provide practical indications for drug implementation, to be applied not only by cardiologists but also by GPs and internal medicine doctors.